2015
DOI: 10.1161/strokeaha.114.006825
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of the High-Mobility Group Box 1 Protein-Receptor for Advanced Glycation End-Products Signaling Pathway in Rats During Neurogenesis After Intracerebral Hemorrhage

Abstract: 500I ntracerebral hemorrhage (ICH) accounts for roughly 15% of all strokes and is associated with mortality rates approaching 50%; survivors are often left with serious disability.1 The brain responds to ICH in complex ways that involve pathophysiological responses, such as excitotoxicity, free radical damage, and inflammation. Moreover, the brain initiates remodeling processes, such as neurogenesis, angiogenesis, and synaptic plasticity, designed to restore neurological function after ICH.2-4 As part of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Interestingly, the administration of anti-HMGB1 neutralizing mAb has been shown to protect the BBB and to inhibit the inflammation cascade in rat models of middle cerebral artery occlusion/reperfusion-induced infarction and fluid percussion-induced traumatic brain injury111213. The recent studies also reported the increase in HMGB1 levels in peri-hematomal regions in subacute phase after ICH in rats181920, however, there was little information about the acute dynamics of HMGB1 in the core area after ICH. Moreover, whether anti-HMGB1 mAb can also provide neuroprotective effects in a rat model of ICH remains to be seen.…”
mentioning
confidence: 99%
“…Interestingly, the administration of anti-HMGB1 neutralizing mAb has been shown to protect the BBB and to inhibit the inflammation cascade in rat models of middle cerebral artery occlusion/reperfusion-induced infarction and fluid percussion-induced traumatic brain injury111213. The recent studies also reported the increase in HMGB1 levels in peri-hematomal regions in subacute phase after ICH in rats181920, however, there was little information about the acute dynamics of HMGB1 in the core area after ICH. Moreover, whether anti-HMGB1 mAb can also provide neuroprotective effects in a rat model of ICH remains to be seen.…”
mentioning
confidence: 99%
“…However, in myocardial IR, TLR2 is not required for IL-6 (37) and may or may not be required for TNFα production (37, 38). Finally, after intracerebral hemorrhage, HMGB-1 appears to stimulate TLR2 and TLR4 and provide a beneficial neurogenesis at later time points (39). …”
Section: Discussionmentioning
confidence: 99%
“…High mobility group box1 (HMGB1) is a highly conserved non-histone DNA-binding nuclear protein that is ubiquitously expressed in eukaryotic cells and regulates transcription [5]. HMGB1 promotes inflammatory injury [6, 7] by inducing the expression of cytokines such as IL-1β, IL-6, and inflammation-related enzyme inducible nitric oxide synthase (iNOS) [4, 810], which are known to play key roles in the development of brain I/R [1114].…”
Section: Introductionmentioning
confidence: 99%